2019
DOI: 10.1177/0300985819879442
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Myocardial Fibrosis in Captive Chimpanzees (Pan troglodytes)

Abstract: Cardiovascular disorders and predominantly idiopathic myocardial fibrosis are frequently associated with mortality among zoo-housed chimpanzees ( Pan troglodytes). Formalin-fixed whole hearts of deceased chimpanzees housed in zoos ( n = 33) and an African sanctuary ( n = 2) underwent detailed macroscopic and histopathologic examination using a standardized protocol. Archived histological slides from the hearts of 23 additional African sanctuary-housed chimpanzees were also examined. Myocardial fibrosis (MF) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 47 publications
4
31
0
Order By: Relevance
“…It is possible that vitamin D de ciency is a signi cant risk factor for cardiac disease in zoo-housed chimpanzees as macrophage-mediated brosis has been shown to induce differentiation of cardiac stromal cells into myo broblasts [53][54][55] . A brosis-associated increase of macrophages and myo broblasts was also shown in a previous study in chimpanzees 11 . Considering the results of this study, together with the high prevalence of idiopathic myocardial brosis (IMF) in chimpanzees 11 , a relationship between vitamin D status and cardiovascular disease seems plausible.…”
Section: Discussionsupporting
confidence: 81%
“…It is possible that vitamin D de ciency is a signi cant risk factor for cardiac disease in zoo-housed chimpanzees as macrophage-mediated brosis has been shown to induce differentiation of cardiac stromal cells into myo broblasts [53][54][55] . A brosis-associated increase of macrophages and myo broblasts was also shown in a previous study in chimpanzees 11 . Considering the results of this study, together with the high prevalence of idiopathic myocardial brosis (IMF) in chimpanzees 11 , a relationship between vitamin D status and cardiovascular disease seems plausible.…”
Section: Discussionsupporting
confidence: 81%
“…A wide range of clinical conditions specific to primates have thus been studied in sanctuary settings. Cardiac function [198] and disease [199,200] have been investigated in both chimpanzees and bonobos, as well as improvements to cardiac monitoring [201] and heart rate responses to anaesthetic protocols [202]. At Kumamoto, clinical cases of maxillary sarcoma [203], leprosy [204] and Down syndrome [205] have all been reported in chimpanzees, while researchers have also investigated a non-invasive test for tuberculosis in PASA sanctuaries [206].…”
Section: (C) Veterinary Genetic and Physiologymentioning
confidence: 99%
“…The lack of sex differences for intrinsic and extrinsic etiologies in this study is especially noteworthy in regard to cardiac-related deaths, which made up 47% of female deaths and 51% of male deaths in this study sample. Strong et al [ 72 ] also reported a similar finding of males and females being affected by cardiac disease (specifically idiopathic myocardial fibrosis) at similar frequencies. This is in contrast to previous findings, which suggested a much more prevalent link between cardiac issues and sex, with males being much more affected [ 73 ].…”
Section: Discussionmentioning
confidence: 67%